2008
DOI: 10.1016/j.neuro.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of selective dopamine uptake inhibitors, GBR 12909 and WIN 35428, on HIV-1 Tat toxicity in rat fetal midbrain neurons

Abstract: Drug abuse is a risk factor for neurological complications in HIV infection. Cocaine has been shown to exacerbate HIV-associated brain pathology and enhance neurotoxicity of HIV-1 Tat and gp120 proteins. In this study, we found that the selective inhibitor of dopamine transporter (DAT) function, 1-[2-[bis(4-fluorophenyl) methoxy]ethyl]-4-(3-phenylpropyl) piperazine (GBR 12909, vanoxerine), but not the selective inhibitors of serotonin and norepinephrine (SERT and NET) transporters, sertraline and nizoxetine, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Reduced DA transporter (DAT) levels in the putamen and ventral striatum are found in HIV-1+ individuals with cognitive impairment (Wang et al 2004; Chang et al , 2008). In vitro studies have shown that DAT is targeted by HIV-1 proteins Tat and gp120, resulting in transporter impairment (Aksenov et al 2008; Ferris et al 2009; Midde et al 2013; Zhu et al 2009; Zhu et al 2011), due to direct protein-protein interactions (Zhu et al 2009) involving an allosteric modulation of DAT by the Tat protein (Zhu et al 2011). In addition, DA-dependent signaling has been identified as a mechanism of HIV-1 protein neurotoxicity (Aksenova et al 2006; Silvers et al 2007; Wallace et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced DA transporter (DAT) levels in the putamen and ventral striatum are found in HIV-1+ individuals with cognitive impairment (Wang et al 2004; Chang et al , 2008). In vitro studies have shown that DAT is targeted by HIV-1 proteins Tat and gp120, resulting in transporter impairment (Aksenov et al 2008; Ferris et al 2009; Midde et al 2013; Zhu et al 2009; Zhu et al 2011), due to direct protein-protein interactions (Zhu et al 2009) involving an allosteric modulation of DAT by the Tat protein (Zhu et al 2011). In addition, DA-dependent signaling has been identified as a mechanism of HIV-1 protein neurotoxicity (Aksenova et al 2006; Silvers et al 2007; Wallace et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 Tg rats also display alterations in the DA system, with significantly lower MAO-A levels than control animals, as well as lower levels of tyrosine hydroxylase after treatment with methamphetamine (Moran et al 2012). In vitro studies have shown that DAT is targeted by HIV-1 proteins Tat and gp120, resulting in transporter impairment (Aksenov et al 2008;Ferris et al 2009;Midde et al 2013;Zhu et al 2009;Zhu et al 2011), due to direct protein-protein interactions (Zhu et al 2009) involving an allosteric modulation of DAT by the Tat protein (Zhu et al 2011). In addition, DA-dependent signaling has been identified as a mechanism of HIV-1 protein neurotoxicity (Aksenova et al 2006;Silvers et al 2007;Wallace et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Primary midbrain and hippocampal cell cultures were prepared from 18-day-old Sprague–Dawley rat fetuses as previously described (Aksenov et al 2006; 2008; Aksenova et al 2006; 2009). In brief, both the midbrain and hippocampal regions were rapidly microdissected and incubated for 15 min in a solution of 2 mg/ml trypsin in Ca2+- and Mg2+- free Hanks’ balanced salt solution (HBSS) buffered with 10 mM HEPES (Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Neuronal cell viability was assessed using a microplate reader formatted (Aksenov et al 2006, 2008, 2009; Aksenova et al 2006, 2009; Adams et al 2010) variant of the Live/Dead assay (Molecular Probes, Inc., Eugene, OR). In brief, the cleavage product of calcein AM produces a green fluorescence (F 530 nm ) when exposed to 494-nm light and is used to identify live cells.…”
Section: Methodsmentioning
confidence: 99%